VIRTUAL LEARNING ENVIRONMENT: EFFECT OF BLENDED CLASSROOMS ON THE LISTENING SKILL IN A1 STUDENTS - Magali Arteaga; Diana Rodas (EduLite: Journal of English Education, Literature and Culture, 2018)
In Ecuador, the new regulations of the government demand university undergraduate students reach B2 level before reaching 60% of the total number of credits to continue with their majors (Reglamento de Régimen Académico, 2015). The current study intends to analyze the effect of virtual classrooms in the listening skill of A1 (CEFR) students as a way to enhance the learning of a foreign language by the use of the MOODLE platform of the university. The study consisted of one entire class of 28 participants. In the end, the Cohen coefficient was calculated (-1,25), a multiple linear regression R2 0.548 was also calculated showing that the use of virtual classes is a good tool when teaching a foreign language.